Capacity building program for midwives in maternal mental health through psychoeducation and digital application - Evi Kurniasari Purwaningrum; Alfiesyahrianta Habibie; Siti Khotimah; Sherli Yunita; Afgani Raj Muharman Saputra; Bayu Aji Santoso; Nuryan Ayu (University of Merdeka Malang, 2025)
Maternal mental health issues are a critical contributor to the high Maternal Mortality Rate in East Kalimantan. Significant challenges in providing adequate support stem from limited psychological services and knowledge gaps among midwives at the Trauma Center Community Health Center (Puskesmas). This community service research aimed to build the capacity of midwives to provide Psychological First Aid (PFA) for pregnant women through a digitally supported psychoeducation program. The methodology involved a psychoeducation program delivered to 30 midwives, featuring a PFA workshop and the socialization of the